Conservatism of funeral rites of the western Balts - V.I. Kulakov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The phenomenon of conservative spiritual culture of the Balts was studied using the archaeological evidence and Prussian folklore. The autochthonous inhabitants of the Baltic States in the New and Recent History were distinguished by the constancy of their cultural views. In the paper, an attempt was made to find out the deep roots of this unique conservatism in the historical retrospect. In particular, this healthy commitment to constancy, the unwillingness to make changes to the established traditions, was clearly reflected in the funeral rite of the inhabitants of the south-eastern Baltic. Earlier, I have already noted the desire of the Prussians to preserve the connection of times during funeral ceremonies and the presence of a long memory of their predecessors, which is reflected in the cult reverence. The specific theme of this paper is a unique aspect of the Prussian funeral ceremonies – equestrian competitions during the funeral. The paper introduces a fragment of the text dating back to the middle of the 16th century, which contains eyewitness accounts of the unique features of the rituals of the Western Balts in the Reformation era. A parallel was drawn between these features and the data of the merchant Wulfstan on the funerary jumps of the Prussians of the 9th century. In the early Middle Ages, the winner of funeral races received a significant part of the property of the buried tribesman, while the prize-winner in the Prussian funeral arrivals during the era of the Reformation was symbolically enriched only with a small change of one shilling. It was suggested that for seven centuries the inhabitants of the southeastern Baltic States maintained the custom of horse racing at the funeral ceremony, but its sacred meaning on the threshold of the New Age could be lost. Nevertheless, this indirectly confirms V.N. Toporov’s hypothesis on the deep meaning of this phenomenon.